Key determinants of induced abortion in women seeking postabortion care in hospital facilities in Ouagadougou, Burkina Faso - Ilboudo PGC; Somda SMA; Sundby J (Dove Medical Press, 2014)
Patrick GC Ilboudo,1–3 Serge MA Somda,4 Johanne Sundby3 1Département de Santé Publique, Unité de Recherche sur les Politiques et Systèmes de Santé, Centre Muraz, Bobo-Dioulasso, Burkina Faso; 2Agence de Formation, de Recherche et d'Expertise en Santé pour l'Afrique (AFRICSanté), Bobo-Dioulasso, Burkina Faso; 3Department of Community Medicine, University of Oslo, Oslo, Norway; 4Département des Maladies Non Transmissibles, Unité de Formation et d'Appui Méthodologique, Centre Muraz, Bobo-Dioulasso, Burkina Faso Introduction: Despite the universal recognition of unsafe abortion as a major public health problem, very little research has been conducted to document its precipitating factors in Burkina Faso. Our aim was to investigate the key determinants of induced abortion in a sample of women who sought postabortion care. Materials and methods: A cross-sectional household survey was carried out from February to September 2012 in Ouagadougou, Burkina Faso. Data of 37 women who had had an induced abortion and 267 women who had had a spontaneous abortion were prospectively collected on sociodemographic characteristics, pregnancy and birth history, abortion experience, including previous abortion experience, and selected clinical information, including the type of abortion. A two-step regression analysis consisting of a univariate and a multivariate logistic regression was run on Stata version 11.2 in order to identify the key determinants of induced abortion. Results: The findings indicated that 12% of all abortions were certainly induced. Three key factors were significantly and positively associated with the probability of having an induced abortion: whether the woman reported that her pregnancy was unwanted (odds ratio [OR] 10.45, 95% confidence interval [CI] 3.59–30.41); whether the woman reported was living in a household headed by her parents (OR 6.83, 95% CI 2.42–19.24); and if the woman reported was divorced or widowed (OR 3.47, 95% CI 1.08–11.10). On the contrary, being married was protective against induced abortion, with women who reported being married having an 83% (OR 0.17, CI 0.03–0.89) lower chance of having an induced abortion, even when the pregnancy was unwanted. Conclusion: This study has identified three major determinants of induced abortion in Ouagadougou, Burkina Faso. Improved targeted programs on family planning counseling, methods of contraception, and availability of contraceptives should be widely promoted. Keywords: induced abortion, determinants, logistic regression, unwanted pregnancy, cross-sectional study